Brasil e OCDE: Avaliaç\~ao da eficiência em sistemas de saúde - Alexandre Marinho; Simone de Souza Cardoso; Vivian Vicente de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– We evaluate the efficiency of expenditure in health care provision by comparing various output measures (life expectancy; infant survival rate; years of life recovered from diseases; population; area) from the health system of Brazilian and OECD countries with an expenditure measure (health expenditure per capita). When estimating the efficiency frontier and country rankings we combine data envelopment analysis with stochastic frontiers. Our results provide some evidence that Brazil is not in the worst position in the sample.
Keywords: C01; C61; H51; I18; 330; Gesundheitswesen; Gesundheitskosten; Brasilien; OECD-Staaten